The Effectiveness of Developing Problem-Solving Oriented Digital E-Modules on Theme 7: Events in Life for Grade V Elementary School - Sulfiana Firman; Nurlina; Rahmawati; Ma’ruf; Muh Erwinto Imran (Didaktika: Jurnal Kependidikan, 2024)
This research aims to produce instructional materials in the form of a problem-solving oriented digital e-module for fifth-grade elementary school students on the theme "Events in Life" that are valid, practical, and effective. The type of research used is development research using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The subjects of the study are 26 fifth-grade students. The instrument used to measure the effectiveness of the problem-solving oriented digital e-module is a learning outcome test in the form of 10 essay questions. The effectiveness of the problem-solving oriented digital e-module is assessed based on the difference between pretest and post-test learning outcomes analyzed through N-Gain. The N-Gain analysis result is 0.77, which falls into the high category. Based on the N-Gain coefficient, it can be concluded that the problem-solving oriented digital e-module is effective. The implication of this research is that this problem-solving oriented digital e-module can serve as a reference in the development of digital e-modules for other themes or topics in science learning at the elementary school level. It can also be developed for different grade levels and subjects.